FIBRE-REINFORCED POLYMER BARS IN PRECAST SLABS FOR ROADS TO OIL AND GAS EXTRACTION COMPLEXES - Voskobiynyk, S. P. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Considered an example of the application of fibre-reinforced polymer bars in precast slabs for temporary roads to oil and gas extraction complexes. Found that samples of products by geometric requirements similar Ferro-concrete products, but reinforced fibre-reinforced polymer bars accessories instead of metal. The results of replacing metal fittings on the fibre-reinforced polymer bars in the experimental samples. Given the comparative assessment of the conformity of prototypes of requirements on indicates the ability and crack resistance from. Found that fibre-reinforced polymer bars valves may be used in the construction of a prefab temporary roads without reducing their carrying capacity. It is proven that the use of this rebar for reinforcement of structures that work on resilient basis, both at the stage of manufacture and operation. It is shown that the resulting experience can be used in the planning and in the design, manufacture and test prototypes, and the analysis of the obtained results allow you to identify opportunities for the implementation of this direction in Ukraine.